Tantangan Regenerasi Kepemimpinan Muda di Gereja Bala Keselamatan: Tinjauan Sosiologis Berdasarkan Teori Otoritas Max Weber - Mikael Mikael; Riris Johanna Siagian; Arzety Gultom; Yoel Peranginangin; Elvioni Elvioni; Samuel Yohanda R. Silaen (CV. Denasya Smart Publisher, 2026)
This study aims to examine the challenges of youth leadership regeneration in the Salvation Army Church of Pematang Siantar Corps using the perspective of Max Weber's authority theory. Through a descriptive qualitative approach using interview and questionnaire methods, this study found a clash between the church's rigid legal-rational authority structure and the sociological reality of today's youth. Senior leaders tend to perceive the lack of participation as apathy and shifting priorities among working youth. However, the data reveals that youth are actually experiencing a crisis of self-confidence, constrained by rigid hierarchical rules, and lacking youth role models. The novelty of this research lies in offering a resolution to this bureaucratic conflict through a structured mentoring approach and the implementation of Servant Leadership. In conclusion, regeneration will not be effective solely by relying on a formal bureaucratic system; it fundamentally requires holistic guidance, a personal approach, and the humility of leaders to embrace the next generation.